Problems with the Implementation of Cyber Notary in Carrying Out the Duties of Notary Positions in Indonesia - Sujanoko, Guntur (TABELLIUS: Journal of Law, 2024)
This research aims to analyze: 1) The effectiveness of the application of cyber notary in carrying out the duties of a notary position, namely that the application of notary authority can be completed quite quickly and saves time, the application of transactions, namely the preparation of deeds or agreements is limited to electronic documents but all parties can carry out business transactions, avoiding their issuance. costs because there are no transportation obstacles and costs can be calculated, or something crucial related to public services can be provided more effectively and efficiently than through traditional services. When you prepare the deed electronically, you can avoid incurring costs. The notary and presenter meet via electronic video conference, the notary and presenter are limited to seeing a computer at their place without having to pay any expenses to travel. This usually has an impact on the efficiency of the time required, through digitalization changes, everything can be maximized and save time. 2) Legal certainty of notarial deeds based on cyber notary, namely legal certainty can be achieved if there are no conflicting provisions between one law and another.  Providing Notary services that utilize technological advances in making authentic Deeds in cyberspace (Cyber notary) is possible for Notaries in Indonesia based on the Elucidation of Article 15 Paragraph (3) of the new UUJN, however the implementation of Cyber notary is still in conflict with the existing Law. one with another so that it does not provide a guarantee of legal certainty. Notarial Deeds made electronically (Cyber notary) do not yet have legal certainty because there is no harmonization of regulations related to the authority of Notaries in making Deeds electronically as stated in the UUJN in conjunction with the new UUJN and the ITE Law. This is what makes Notaries afraid to provide services that utilize technological advances in making authentic Deeds in cyberspace (Cyber notary).